Polyphenol-rich spice-based beverages modulated postprandial early glycaemia, appetite and PYY after breakfast challenge in healthy subjects: A randomized, single blind, crossover study - Zanzer, Yoghatama C.; Plaza, Merichel; Dougkas, Anestis; Turner, Charlotta; Björck, Inger; Östman, Elin (Journal of functional foods, 2017)
[Display omitted] •Turmeric and cinnamon reduced early glycaemia without affecting insulin.•Turmeric increased serum PYY up to 180min after intake.•‘Desire to eat’ and ‘prospective consumption’ was reduced by spice-based beverages.•By offering glucose lowering effects, certain spices may be important in lowering cardiometabolic risk. Spices are rich in distinct polyphenols which might act on the gut by inhibiting glucose uptake and modulating appetite responses. To investigate this hypothesis, healthy adults were randomly assigned to receive isovolumetric (220ml) spice-based (contained total polyphenol concentration to 185mg gallic-acid equivalents) or control beverages followed by a standard bread breakfast containing 50g available carbohydrates in a cross-over trial. Postprandial glucose, insulin, PYY and appetite responses were evaluated. Ultra-high-performance liquid chromatography coupled to electrospray quadrupole time-of-flight mass spectrometry (UHPLC-DAD-ESI-QTOF-MS) was used for polyphenols profiling. Cinnamon and turmeric lowered early blood glucose increment up to 45min compared to control. Turmeric increased p-PYY and lowered ‘desire to eat’ and ‘prospective consumption (quantity of food wanted to it)’ compared to control. By offering appetite modulation and glucose lowering effects, certain spices (e.g. turmeric and cinnamon) may be important in lowering cardiometabolic risk.